Ventilator-Induced Diaphragm Dysfunction (Review) - M. A. Babaev (Obŝaâ Reanimatologiâ, 2018)
Mechanical ventilation is associated with a number of complications that increase the cost of treatment and the hospital mortality rate. In 2004, the term «ventilator-induced diaphragm dysfunction» (VIDD) was proposed to explain one of the reasons for the failure of respiratory support. At present, this term is understood as a combination of atrophy and weakness of the contractile function of the diaphragm caused directly by a long-term mechanical lung ventilation. Oxidative stress, proteolysis, mitochondrial dysfunction, as well as passive overdistension of the diaphragm fibers contribute greatly to the pathogenesis of VIDD. Since 30—80% of patients in the ICU require mechanical respiratory support and even 6—8 hours of mechanical lung ventilation can contribute to the development of a significant weakness of the diaphragm, it can be concluded that the VIDD is an extremely urgent problem in most patients. Its typical clinical presentation is characterized by impaired breathing mechanics and unsuccessful attempts to switch the patient to the spontaneous breathing in the absence of other valid reasons for respiratory disorders. The sonography is the most informative and accessible diagnostic method, and preservation of spontaneous breathing activity and the use of the latest mechanical ventilation modes are considered a promising approach to prevention and correction of the disorders. The search for an optimal strategy for lung ventilation, development of diagnostic and physiotherapeutic methods, as well as the consolidation of the work of a multidisciplinary team of specialists (anesthesiologists and intensive care specialists, neurologists, pulmonologists, surgeons, etc.) can help in solving this serious problem. A review of 122 sources about the VIDD presented data on the background of the issue, the definition of the problem, etiology and pathogenesis, clinical manifestations, methods of diagnosis, the effect of drugs, prevention and therapy.